Basic College Mathematics (9th Edition)

Published by Pearson
ISBN 10: 0321825535
ISBN 13: 978-0-32182-553-7

Chapter 9 - Basic Algebra - 9.7 Solving Equations with Several Steps - 9.7 Exercises: 74

Answer

$z = 24$

Work Step by Step

$\frac{z}{3} + 1 = \frac{z}{2} -3$ $z + (1 \times 3) = \frac{z \times 3}{2} - (3 \times 3)$ $z + 3 = \frac{3z}{2} - 9$ $(z \times 2) + (3 \times 2) = 3z - (9 \times 2)$ $2z + 6 = 3z - 18$ $-z + 6 = -18$ $-z = -24$ $z = 24$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.